Step by step procedures: Degradation of polycyclic aromatic hydrocarbons in potable water using photo-Fenton oxidation process - Abd Manan T.S.B.; Beddu S.; Khan T.; Wan Mohtar W.H.M.; Sarwono A.; Jusoh H.; Mohd Kamal N.L.; Sivapalan S.; Ghanim A.A.J. (Elsevier B.V., 2023)
drinking water; ferrous gluconate; polycyclic aromatic hydrocarbon; aqueous solution; Article; chemical oxygen demand; degradation; electrolysis; Fenton reaction; landfill leachate; leaching; municipal solid waste; photooxidation; priority journal; soil pollution; soil treatment; total organic carbon; ultraviolet irradiation; waste component removal; waste water management